Nutritional risk and HbA1c as critical risk factors and predictors of opportunistic infections in HIV-DM comorbid patients: a retrospective cross-sectional study - Zhu, Qiong’e; Gao, Fengjiao; Ren, Xiaoxia; Li, Rui; Kang, Jun; Li, Maoquan; Liu, Dafeng (Frontiers in Endocrinology, 2025)
BackgroundThe clinical characteristics and risk factors for opportunistic infections in HIV patients with concomitant diabetes mellitus are unclear and worth studying. Explore the risk factors and construct a predictive model for opportunistic infections in HIV-DM patients.MethodsClinical data were retrospectively collected from 1,669 HIV-DM admitted to the Public Health Clinical Center of Chengdu from December 2018 to November 2023.Based on the occurrence of opportunistic infections, the patients were divided into two groups. Comparative analyses were conducted to assess nutritional status, plasma glucose levels, comorbidities of chronic noncommunicable diseases, and immune status. We applied univariate logistic regression and LASSO regression to screen independent variables. Multivariable logistic regression analysis was performed to identify risk factors and establish a prediction model for opportunistic infections.ResultsIn our study population of 1,669 patients (median age was 59 years, 83.22% male), 868 developed opportunistic infections, while the remaining 801 patients did not develop opportunistic infections. Additionally, 1,598 patients survived, and 71 patients died. The opportunistic infection group had a greater median age, lower median BMI, longer median length of hospital stay and greater number of deaths. Logistic regression analysis identified nutritional risk, duration of HIV infection, HbA1c, albumin, and CD4+ T cell counts as significant risk factors and predictors of opportunistic infections. Nutritional risk (OR=2.888) and HbA1c showed positive associations (P<0.001), while duration of HIV infection, albumin, and CD4+ T cell counts demonstrated negative associations with infection risk (P<0.05). The comprehensive model evaluation, based on receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA), validated the acceptable predictive performance of our model.ConclusionThis study identified nutritional risk, duration of HIV infection, HbA1c and albumin as significant risk factors and predictors of opportunistic infections in HIV-DM patients, further highlighting the importance of nutritional screening and good glucose control.